PENGGUNAAN APLIKASI TIKTOK SHOP DALAM BELANJA ONLINE SANTRI NURUL ICHSAN BONTANG - Khusnaini, Rosadi (JDARISCOMB: Jurnal Komunikasi dan Penyiaran Islam, 2023)
Nowadays, when you want to go shopping, you don't have to bother going outof the house. It is enough to have a gadget and download the TikTok application,so you can search for the current products you are looking for. Only by swipingthe gadget screen, if you are interested in the image catalog displayed, thenclick shopping. Payment can be transferred directly or paid on the spot. AtNurul Ichsan Islamic Boarding School every day there are couriers deliveringpackages to the students. Some use the COD payment method or pay on thespot, some have paid directly via transfer, and some have paid in installments.The items purchased by the students also varied. Starting from learningequipment such as mushafs of the Koran, clothes such as robes and modernclothes, cosmetics and beauty tools such as skincare, to even buying lato-latoviral games through the TikTok shop. even the couriers are very familiar withthe students who often shop online because every day there are shipments ofgoods to Islamic boarding schools, both male students and female students. So,from the large number of students who shop online and the frequent courierscoming to deliver packages to Islamic boarding schools, I wrote this researchso that it becomes a lesson and education for students, so they don't becomeconsumptive or wasteful in spending things that are not needed. With thisresearch, it is an appeal to students so that what is spent is in accordance withwhat is needed, not just desires, following the trend that is currently viral, sothat the money does not run out in vain. Not redundant, because redundant is afriend of satan. Santri are expected to be able to dampen their passions so theyare not affected by the temptations of online shopping. Sekarang ini mau belanja tidak perlu repot-repot pergi keluar rumah. Cukupdengan memiliki hp dan mendownload aplikasi TikTok, maka sudah bisamencari produk-produk kekinian yang dicari. Hanya dengan mengusap layarhp, tertarik dengan katalog gambar yang ditampilkan, lalu klik belanja. Pembayaran bisa ditransfer langsung atau bayar di tempat. Di pondokpesantren Nurul Ichsan setiap hari ada saja kurir mengantarkan paket santri.Ada yang menggunakan metode pembayaran COD atau bayar di tempat, adayang sudah bayar langsung melalui transfer, dan juga ada yang dicicilpembayarannya. Barang-barang yang dibelanjakan oleh santri-santri punberagam. Mulai dari perlengkapan belajar seperti mushaf Alquran, pakaianseperti gamis jubah dan baju-baju kekinian, kosmetik dan alat-alat kecantikanseperti skincare, sampai beli permainan viral lato-lato pun melalui TikTokshop. bahkan kurir sudah hafal sekali dengan santri-santri yang sering belanjaonline karena setiap hari ada saja kiriman barang ke pondok pesantren, baiksantri putra dan santri putri. Maka dari banyaknya santri-santri yang belanjasecara online dan seringnya kurir datang mengantarkan paket barang kepondok pesantren maka saya menulis penelitian ini agar menjadi pelajaran danpendidikan untuk santri, agar tidak menjadi konsumtif atau boros dalammembelanjakan barang yang tidak diperlukan. Dengan penelitianini,merupakan himbauan kepada santri agar apa yang dibelanjakan sesuaidengan yang dibutuhkan, bukan hanya keinginan, mengikuti trend yangsementara sedang viral saat ini, sehingga uangnya habis percuma. Tidakmubazir, karena mubazir itu adalah temannya setan. Santri diharapkan bisameredam hawa nafsunya agar tidak terpengaruh oleh godaan-godaan belanjaonline.